Nanodefects in YAG:Ce-Based Phosphor Microcrystals - Victor Lisitsyn; Ludmila Lisitsyna; Aida Tulegenova; Yangyang Ju; Elena Polisadova; Evgeniy Lipatov; Vitaliy Vaganov (Crystals, 2019)
The present paper focused on the study of spectral−kinetic characteristics of luminescence in two batches of yttrium aluminum garnet (YAG):Ce-based phosphors synthesized in different years by two manufacturers: NPO “Platan” in Russia and “GrandLux” in the People’s Republic of China (PRC). Upon studying the structural characteristics of the phosphors—elemental composition, morphology, and X-ray diffraction (XRD) patterns—it was concluded that both types of YAG:Ce phosphors are highly imperfect. The presence of heterogeneities of different nature was accompanied by the introduction—to compensate for charges and elastic stresses—of intrinsic lattice defects during synthesis. There is a high probability of creating complex defects during phosphor synthesis. Luminescence properties (full width at half maximum (FWHM), spectral position of the emission peaks, excitation spectra of emission, emission decay time) are affected by the nearest environment of the luminescence center; whereas the degree of correlation of defects (distance between the components of the donor−acceptor pair) does not depend on the concentration of impurities, intrinsic defects, and their ratio. The results do not fit into the framework of existing ideas regarding the processes in phosphors as systems with widely distributed luminescence centers. The patterns obtained in the paper are discussed based on a hypothesis according to which a nanodefect phosphorus crystal phase is formed during the synthesis.